The Influence of Sustainable Supplier Management Practices on Organizational Performance: A Case of Dodoma Quality Furniture in Tanzania - Magreth Felix; Ismail Changalima; Goodluck Ntangeki (International Journal of Management, Accounting and Economics)
Despite the growing attention to sustainability in supply chain management, empirical evidence on how sustainable supply chain practices directly influence organizational performance, particularly from the perspective of developing countries, remains limited. To fill this gap, the study examines the influence of sustainable supplier management practices on organizational performance. The study relied on the data obtained through structured questionnaires from randomly selected 80 respondents from Dodoma quality furniture located in Dodoma city, Tanzania. The collected data were analyzed by using descriptive and multiple linear regression analysis in IBM SPSS version 25. The findings reveal that sustainable supplier management practices, including sustainable supplier selection, sustainable supplier integration, and sustainable supplier monitoring, are perceived as relevant in a manufacturing firm. Furthermore, the findings indicate that sustainable supplier selection, sustainable supplier integration, and sustainable supplier monitoring are positively and significantly related to organizational performance. These findings confirm that sustainable supplier management practices are critical determinants of organizational performance in the context of a manufacturing firm. The study emphasizes prioritizing sustainability in supply chain management to enhance long-term performance and gain a competitive edge in environmentally conscious markets. The positive role of sustainable supplier management practices on organizational performance urges policymakers to develop comprehensive policies supporting sustainable supplier practices, enabling organizations to achieve economic, environmental, and societal benefits while navigating competitive challenges.